(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This article is the result of the strand of Bahia of the inter-institutional research Schools of Arts and Crafts in Brazil: history, training proposals and continuities in the formation of the Bachelor of Fashion Design. Of a qualitative nature, the research prioritizes a historical investigation, analyzing the Liceu de Artes e Ofícios da Bahia (1872-2007), its beginnings and development, searching for clothing activities, such as cutting and sewing. We try to understand the role of the institution in the formation of citizens, especially from the social conjuncture that existed at the time of its emergence, of a population recently freed from slavery in a city in the process of industrialization. In addition, it seeks to understand what role the Liceu plays in soteropolitan society, especially in the 1990s and 2000s, inquiring if it had as direction the teaching of cloth modeling and sewing. Methodologically, we used as main resource the bibliographic research, gathering information about the institution and the socio-educational context of Bahia through the works of Cunha (1979), Leal (1996), Trinchão (2008) and Reis (2012), with support in a questionnaire with some professionals who worked at the institution in the most recent period. It is concluded that the Liceu de Artes e Ofícios da Bahia perpetuated its main objective of assisting and instructing economically disadvantaged classes. There was no further development of activities related to clothing practices, of which only traces were found. In its last years, the Liceu promoted citizen education through the arts.